Exploring the Perceptions of EFL Lecturers toward Agile Pedagogy in Indonesian Higher Education - Khusnul Harsul Lisan; Nunuk Melisa (EXPOSE (Journal of English Education and for Specific Purpose), 2026)
This study explores the perceptions of English as a Foreign Language (EFL) lecturers toward agile pedagogy at the Department of English Language Education, Universitas Nahdlatul Ulama (UNU) Yogyakarta, Indonesia. Yet its potential in EFL contexts, particularly in Indonesian higher education where instructional cultures remain largely examination-driven and innovation-resistant, has received almost no empirical attention. Motivated by the near-absence of empirical research on agile pedagogy in EFL and non-STEM contexts, particularly within Indonesian Islamic higher education, this study employed a qualitative descriptive design using semi-structured interviews with five to eight purposively selected EFL lecturers. Thematic analysis following Braun and Clarkes (2006) six-phase framework revealed four key themes: (1) limited familiarity with agile pedagogy concepts, (2) perceived potential of agile pedagogy for EFL skills development particularly in speaking and writing, (3) perceived challenges to implementation rooted in curricular rigidity and professional workload pressures, and (4) moderate readiness with conditional willingness to adopt. The findings indicate that while lecturers are largely unfamiliar with agile pedagogy as a formal framework, they demonstrate intuitive alignment with its core values once introduced. Structural barriers particularly rigid semester learning plans (RPS), examination-driven assessment systems, and Tri Dharma Perguruan Tinggi obligations emerged as primary impediments to adoption. This study contributes the first empirically grounded account of EFL lecturers perceptions of agile pedagogy in an Indonesian Islamic university context, offering practical implications for professional development design and institutional policy reform, and establishing a baseline for future interventionist research.